PROGRAM PELATIHAN KEWIRAUSAHAAN PADA GURU TK “ IT AL-MA’UN” DI JALAN ASPARAGA NO.25 SENGKALING DAU MALANG - Bakhrudin Bakhrudin; Anik Kusmintarti; M. Arief Setiawan; Sigit Budisantoso (Jurnal Pengabdian kepada Masyarakat, 2020)
Community Service is one of a lecturer’s duties in the Three Services of Higher Educational Institution. A lecturer has to do the three duties mentioned in the regulation (lecturing, conducting researches, and doing community services). The main objective of conducting this entrepreneurship training programme is to make the teachers in TK IT Al Ma’un able to grab business opportunities in the society to give them additional income. The method planned for this programme is by giving the teachers a training on entrepreneurship entitled How to Start A Business. The steps of the programme are as follows: preparation, implementation, followed with question and answer session. Seen from the implementation of the community service done on August 15, 2018 in TK IT Al Ma’un Jl Asparagus 25 Sengkaling Dau Malang, it could be said that the teachers were excited in joining the programme. Many teachers asked a lot of questions about the programme.Keywords: